Determinants of Firm Value in the Indonesian Property and Real Estate Sector: Evidence from Panel Data Analysis (2013-2024) - Taufik Hidayat; Adibah Yahya; Eka Avianti Ayuningtyas; Oom Tikaromah (Owner : Riset dan Jurnal Akuntansi, 2025)
This study analyzes how Good Corporate Governance (GCG), specifically through the audit committee, capital structure (DER), profitability (ROE), and firm size, influences firm value within Indonesia's property and real estate sector. By examining secondary data from companies' annual reports between 2013 and 2024 using panel data regression, and sample selection using purposive sampling. The findings indicate that the audit committee does not significantly influence firm value, suggesting its role is more supervisory than directly strategic in value creation. Conversely, capital structure (DER) shows a positive effect on firm value, implying that efficient debt utilization can enhance shareholder returns. Profitability (ROE) also positively impacts firm value, confirming that strong financial performance and operational efficiency boost investor confidence. Interestingly, firm size negatively affects firm value, possibly due to operational complexities and inefficiencies often associated with larger corporations. These insights offer valuable guidance for investors and management in understanding the determinants of firm value in this sector.